Evaluation of an Opt-Out Protocol for Antibiotic De-Escalation in Patients With Suspected Sepsis: A Multicenter, Randomized, Controlled Trial. (28th September 2022) - Moehring, Rebekah W; Yarrington, Michael E; Warren, Bobby G; Lokhnygina, Yuliya; Atkinson, Erica; Bankston, Allison; Collucio, Julia; David, Michael Z; Davis, Angelina E; Davis, Janice; Dionne, Brandon; Dyer, April P; et al.
Abstract: Background: Sepsis guidelines recommend daily review to de-escalate or stop antibiotics in appropriate patients. This randomized, controlled trial evaluated an opt-out protocol to decrease unnecessary antibiotics in patients with suspected sepsis. Methods: We evaluated non–intensive care adults on broad-spectrum antibiotics despite negative blood cultures at 10 US hospitals from September 2018 through May 2020. A 23-item safety check excluded patients with ongoing signs of systemic infection, concerning or inadequate microbiologic data, or high-risk conditions. Eligible patients were randomized to the opt-out protocol vs usual care. Primary outcome was post-enrollment antibacterial days of therapy (DOT). Clinicians caring for intervention patients were contacted to encourage antibiotic discontinuation using opt-out language. If continued, clinicians discussed the rationale for continuing antibiotics and de-escalation plans. To evaluate those with zero post-enrollment DOT, hurdle models provided 2 measures: odds ratio of antibiotic continuation and ratio of mean DOT among those who continued antibiotics. Results: Among 9606 patients screened, 767 (8%) were enrolled. Intervention patients had 32% lower odds of antibiotic continuation (79% vs 84%; odds ratio, 0.68; 95% confidence interval [CI], .47–.98). DOT among those who continued antibiotics were similar (ratio of means, 1.06; 95% CI, .88–1.26). Fewer intervention patients were exposed to extended-spectrum antibiotics (36% vs 44%). Common reasons for continuing antibiotics were treatment of localized infection (76%) and belief that stopping antibiotics was unsafe (31%). Thirty-day safety events were similar. Conclusions: An antibiotic opt-out protocol that targeted patients with suspected sepsis resulted in more antibiotic discontinuations, similar DOT when antibiotics were continued, and no evidence of harm. Clinical Trials Registration: NCT03517007. Abstract : In this randomized trial, we evaluated the effect of opt-out intervention among selected, noncritically ill hospitalized adults with suspected sepsis. The intervention resulted in more antibiotic discontinuations, similar days of therapy when antibiotics were continued, and no evidence of harm.